Genetic dominance of transforming growth factor-β1 polymorphisms in chronic liver disease - Cai, Xuanyan; Zha, Huiyan; Yang, Zhaoxu; Du, Yiwen; Dai, Xiaoyang; Yang, Bo; Wang, Jiajia; He, Qiaojun; Weng, Qinjie (Frontiers in Immunology, 2022)
Chronic liver disease (CLD) is an extremely common clinical condition accompanied by sustained inflammatory response leading to tissue damage. Transforming growth factor-β1 (TGF-β1) is known as a master immune regulator in CLDs, but the association between TGF-β1 polymorphisms and CLD risk is controversial and inconclusive, and the genetic dominance of CLDs remains unknown. In this study, the relationship between TGF-β1 polymorphisms and CLD susceptibility is systematically analyzed based on 35 eligible studies. Individuals with the TGF-β1-509 allele (TT or CT) or codon 10 allele (Pro/Pro) show an increased risk of CLDs. Subgroup analyses indicate TGF-β1-509C/T has a significant correlation with cirrhosis and chronic hepatitis C, codon 10 is associated with chronic hepatitis B occurrence, and codon 25 exhibits a relationship with autoimmune hepatitis risk. Missense mutations in G29E, A105S, D191N, and F321L of TGF-β1 are the genetic factors of HCC susceptibility. Furthermore, the TGF-β1 gene expression is significantly elevated in CLD patients, and the TGF-β1 codon 263 is located close to the region where the TGF-β1 dimerization interacts, indicating the TGF-β1 codon 263 variant may affect the secretion of TGF-β1 by altering its dimerization. Together, our findings provide new insights into the immune regulator gene TGF-β1 polymorphisms as susceptibility factors for CLD occurrence and regulators for TGF-β1 expression, which have implications for the regulation of immune factors during CLD development.